2015
DOI: 10.1039/c5cp03720d
|View full text |Cite
|
Sign up to set email alerts
|

Excess electron reactivity in amino acid aqueous solution revealed by ab initio molecular dynamics simulation: anion-centered localization and anion-relayed electron transfer dissociation

Abstract: Studies on the structure, states, and reactivity of excess electrons (EEs) in biological media are of great significance. Although there is information about EE interaction with desolvated biological molecules, solution effects are hardly explored. In this work, we present an ab initio molecular dynamics simulation study on the interaction and reactivity of an EE with glycine in solution. Our simulations reveal two striking results. Firstly, a pre-solvated EE partially localizes on the negatively charged -COO(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Unfortunately, our approach does not allow determining the reaction barrier. However, a first-principles molecular dynamics (FPMD) study revealed this mode of action as well [ 80 ]. Initially, the electron binds to the carboxyl group of glycine.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, our approach does not allow determining the reaction barrier. However, a first-principles molecular dynamics (FPMD) study revealed this mode of action as well [ 80 ]. Initially, the electron binds to the carboxyl group of glycine.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies involve dynamic cluster models rather than the condensed-phase ones. Interesting per se , reaction mechanisms in clusters can be different from those in the bulk. In some articles, substrates after electron attachments are simulated both in clusters ,, and in the condensed phase, concentrating on relaxation kinetics but omitting the diffusion and electron transfer. Finally, simple generalized gradient approximation (GGA) DFT , is applied for condensed-phase MD, despite the delocalization error.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 18 The representative dielectron clathrate hydrate bi-cavity structure, spin density distribution and the spin coupling pathway of two electrons (a) and the electric field regulated changes of spin denisty and spin coupling contants (b) [76,77] (color online). [63] (网络版彩图) [78] (网络版彩图)…”
Section: 水合电子的回旋半径随时间的演化曲线(图8(a))mentioning
confidence: 99%
“…Figure 20 The simulation of the solvated-electron-induced N−C α bond cleavage process of glycine in the aqueous glycine solution [78] (color online).…”
Section: 水合电子的回旋半径随时间的演化曲线(图8(a))mentioning
confidence: 99%